In Vivo ANTIPLASMODIAL ACTIVITY AND MECHANISM OF ACTION OF 1,10-PHENANTHROLINE DERIVATIVES - ., Mustofa; Yapi, Ange Desire; Valentin, Alexis (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The rapidly increasing resistance of Plasmodium falciparum to the most commonly used antimalarial drug indicates the urgent need for new antimalarial compounds. Previous study showed that among thirteen derivatives of 1,10-phenanthroline, four compounds were active in vitro and potential for further development. The study was conducted to provide the in vivo antiplasmodial activity of four 1,10-phenanthroline derivatives and to evaluate the possibility of their mechanism of action. The in vivo antiplasmodial activity of the four compounds was evaluated by a standard 4-day test on Plasmodium venckei petteri infected mice. The study of haem polymerization inhibitory activity (HPIA) and the potentiating of those compounds in combination with halofantrine and inhibitor protease (E64) were carried out to evaluate its mechanism of actions. The results showed that among four compounds tested, compound 1 (2,10-methyl-3-(2-chloroethyl)-4-chloropirydo [2,3-i] quinolineium iodide) was the most active compound with DE50 was 0.22 ± 0.03 mg/kg BW. This molecule less active than halofantrine, but more active than chloroquine. The HPIA of 1,10-phenanthroline derivatives tested (IC50 HPIA was 1.57-1.95 mmol/well) did not vary significantly. These IC50 HPIA values were significantly lower than halofantrine (CI50 HPIA was 0.12 ± 0.04 mmol/well) and than chloroquine (CI50 HPIA was 0.75 ± 0.03 mmol/well). Combination the 1,10-phenanthroline derivatives and halofantrine produced simple additive effect that implies that each drug posses a different mechanism of action. Conversely, there was antagonist interaction between 1,10-phenanthroline derivatives and E64 showing that the drugs have a similar mechanism of action. It can be concluded that the compound 1 appears as a potential antimalarial compound. In addition, the possible mechanism of action of this compound is inhibitation of protease involved in haemoglobine degradation within the malaria parasite.Key words : 1,10-phenanthroline – in vivo antiplasmodial – haem polymerization inhibitoryactivity – protease inhibitor .